A CNO dichotomy among O2 giant spectra in the Magellanic Clouds - Walborn, Nolan Revere (2004)
From a survey of the 3400 Å region in the earliest O-type spectra, we have found that two of the four O2 giants observed in the Large Magellanic Cloud have O IV lines there that are stronger than the N IV lines, while the other two have the opposite. A Small Magellanic Cloud counterpart also has N IV stronger than O IV. Inspection of the blue spectra of these stars shows that the former pair have weaker N lines in all ionization states (III, IV, and V) present as well as lines of C IV λ4658, while the latter three have stronger N lines and greater He/H. Space ultraviolet observations of two of the N-strong stars show N V wind profiles substantially stronger than those of C IV, while in the N-weak stars the C IV features are equal to or stronger than the N V. The N-strong stars are now reclassified as ON2 III(f *), newly defining that category. These characteristics strongly suggest a larger fraction of processed material in the atmospheres of the ON2 stars, which we confirm by modeling the optical spectra. In the context of current models, it is in turn implied that the ON2 stars are in a more advanced evolutionary state than the others, and/or that they had higher initial rotational velocities. The recent formulation of the effects of rotation on massive stellar evolution introduces an additional fundamental parameter, which the CNO abundances are in principle able to constrain. We present some illustrative comparisons with current Geneva evolutionary models for rotating massive stars. It is possible that these very hot, nitrogen-rich objects are products of homogeneous evolution. Our results will provide motivation for further physical modeling of the atmospheres and evolutionary histories of the most massive hot stars.